I want to prove that $$8^x+4^x\geq 6^x+5^x$$ for all $x\geq 0$. How can I do this?

My attempt:

I try by AM-GM: $$8^x+4^x\geq 2\sqrt{8^x4^x}=2(\sqrt{32})^x.$$

However, $\sqrt{32}\approx 5.5$ so I am not sure if $$2(\sqrt{32})^x\geq 5^x+6^x$$ is true.

Also, I try to compute derivatives but this doesn't simplify the problem. What can I do?

  • 2
    $\begingroup$ That AM-GM simplification isn't going to help you, because for $x$ large enough (larger than about $8.5$, to be more precise), the $6^x$ term will dominate the $\sqrt{32}^x$ term. $\endgroup$ – Arthur Nov 28 at 14:01

Use: $$ 4^x \left(\left(\frac 32\right)^x-1\right) \left(\left(\frac 43\right)^x-1\right) \ge 0 $$ for $x\ge 0$.

  • 1
    $\begingroup$ @Macavity I also got the same result as you. $\endgroup$ – The Demonix _ Hermit Nov 28 at 17:28
  • $\begingroup$ @Macavity: I was trying to match three of the four bases of the power function of the inequality. So: $$4\cdot \frac 32\cdot \frac43=8\ ,$$ $$4\cdot \frac 32\cdot 1=6 $$ $$ 4\cdot 1\cdot 1=4 $$ and the remained product should be stronger than $5$, that one is $$ 4\cdot 1\cdot \frac 43=\frac {16}3>5 \ .$$ $\endgroup$ – dan_fulea Nov 28 at 17:30
  • $\begingroup$ OK - that’s clear now. Thanks. $\endgroup$ – Macavity Nov 28 at 17:35
  • 1
    $\begingroup$ @TheDemonix_Hermit Thanks for the comment, please always ask / insert it in such situations! (It is a good check also for me, some answers - as this one - are a ten seconds shot... So a double check by the community is the thing i want.) I hope the situation is explained and correct now. Since i am also following didactical activities, and need to teach so that errors are prevented by mnemonic mechanisms, please give a hint how you obtained the other four numbers. ($12$ was one of them, nine was - i think - also in the liist.) $\endgroup$ – dan_fulea Nov 28 at 17:56
  • $\begingroup$ @dan_fulea Clearing denominators by multiplying by $6^x$ And expanding will give the other four numbers. The $4^x$ is cancelled as always positive. $\endgroup$ – Macavity Nov 28 at 18:29

Hint. Let $f(t)=t^x$ then by the Mean Value Theorem there is $t_1\in (6,8)$ such that $$f(8)-f(6)=f'(t_1)(8-6)\Leftrightarrow 8^x-6^x=2xt_1^{x-1}.$$ Similarly there is $t_2\in (4,5)$ such that $$f(5)-f(4)=f'(t_2)(5-4)\Leftrightarrow 5^x-4^x=xt_2^{x-1}.$$ It remains to show that for $x\geq 0$ $$2xt_1^{x-1}\geq xt_2^{x-1}.$$

  • 6
    $\begingroup$ Dear downvoter, thank you so much for your useful comments and generous support. $\endgroup$ – Robert Z Nov 28 at 18:34

The function $u\mapsto u+{1\over u}$ is increasing for $u\geq1$. Therefore we have for all $x\geq0$ the chain of inequalities $$8^x+4^x=32^{x/2}\bigl(2^{x/2}+2^{-x/2}\bigr)\geq 30^{x/2}\bigl((6/5)^{x/2}+(6/5)^{-x/2}\bigr)=6^x+5^x\ .$$


Note that $8^x=(6^x)^{\log_6(8)}$ so that \begin{equation}\tag 1\label 14^x+8^x-6^x-5^x\geq 8^x-6^x-5^x\to\infty\end{equation} as $x\to\infty$.

I will show that the only non-negative solution to \begin{equation}\tag 2\label 28^x+4^x=6^x+5^x\end{equation} is $x=0$. Note that $$8^x+4^x=6^x+5^x\iff 8^x-6^x=5^x-4^x.$$

By the Mean value Theorem, we have $8^x-6^x=2x\cdot c^{x-1}$ and $5^x-4^x=x\cdot d^{x-1}$ for some $c\in[6,8]$ and $d\in[4,5]$.

So we have that \eqref{1} is equivalent (for suitable $c$ and $d$) to $$2x\cdot c^{x-1}=x\cdot d^{x-1}.$$ For $x>0$ this is equivalent to $$2=\left(\frac{d}{c}\right)^{x-1}$$ which is impossible since $d\le5<6\le c$. Hence, $x=0$ is the only non-negative solution to \eqref{1}.

From the intermediate value Theorem (and from \eqref{2}), it follows that $8^x+4^x-6^x-5^x>0$ for all $x>0$.


The best and the easiest way to prove it is using Induction .

Base Case :

For $x=1$ , $ 8 + 4 \gt 6+5$

Induction Step :

Let us assume that $8^k +4^k \ge5^k + 6^k$ . This implies that $$8^k \ge (5^k + 6^k) - 4^k$$

Multiplying both the sides by $8$ , we get

$$\color{#f14}{8^{k+1} \ge 8\cdot5^k +8\cdot6^k -8\cdot4^k} \quad \quad \text{(1.)}$$

Now all that is left is to prove that the R.H.S is bigger than $5^{k+1}+6^{k+1}-4^{k+1}$.We prove it by assuming it is true . Then ,

$$\begin{align}8\cdot5^k +8\cdot6^k -8\cdot4^k & \ge 5^{k+1}+6^{k+1}-4^{k+1} \\ 5^k(8-5) + 6^k(8-6) +4^k(4-8) & \ge 0 \\ 3\cdot 5^k +2\cdot6^k - 4\cdot4^k & \ge 0 \\ \color{#2c0}{\left(\frac 34\right)\cdot \left(\frac 54\right)^k + \left(\frac 24\right)\cdot \left(\frac 64\right)^k }& \color{#2c0}{\ge 0 }\quad \quad \text{(2.)}\end{align}$$

which is obviously true for $k \ge 0$ . Hence our initial assumption was true.

Now combining $(1.)$ and $(2.)$ , we get ,

$$\color{#f14}{8^{k+1}} \ge \color{navy}{8\cdot5^k +8\cdot6^k -8\cdot4^k} \ge \color{#2c0}{5^{k+1}+6^{k+1}-4^{k+1}} $$

or $$ 8^{k+1} \ge 5^{k+1} + 6^{k+1} -4^{k+1} \implies \boxed { 8^{k+1} + 4^{k+1} \ge 5^{k+1} + 6^{k+1}}$$

Which completes our induction.

  • 1
    $\begingroup$ How do you prove it for all real $x$, esp $ x \in (0,1)$? $\endgroup$ – Calvin Lin Nov 29 at 9:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.